What Drives User Engagement of Theme Park Apps?: Utilitarian, Hedonic, or Social Gratifications - Long Ting (Switzerland, 2022)
This study seeks to examine the determinants of user engagement in theme park apps from a uses and gratification perspective. Specifically, three different gratifications: utilitarian (i.e., utilitarian value, perceived ease of use, and convenience), hedonic (i.e., hedonic value and curiosity fulfillment), and social (i.e., social interaction and presence) gratifications are proposed to affect user engagement, which comprises three dimensions: cognitive, affective, and behavioral engagement. The research model was tested by collecting data via an online survey (N = 347). The results show that all utilitarian, hedonic, and social gratifications can facilitate users’ cognitive and affective engagement, while behavioral engagement is only affected by utilitarian and hedonic gratification. This study enriches the understanding of what motivates user engagement in theme park apps and offers practical implications for park managers.
Well-Being in the Information Society: When the Mind Breaks: 9th International Conference, WIS 2022, Turku, Finland, August 25–26, 2022, Proceedings